An Analysis of Students’ Ability in Using Personal Pronouns in Narrative Text at Tenth Grade of SMA Swasta Pencawan Medan During Covid-19 Pandemic - Sri Tamba; Rosija Pasaribu; Martauli Pangaribuan; Oktaria Putri Loi; Sri Ninta Tarigan (elt, 2020)
Abstract The research objectives are to find the abilty of the students out in using the personal pronouns in the Narrative Text at Grade Ten of SMA Swasta Pencawan Medan During Covid-19 Pandemic and to know more about the the factors that affect the ability of the students in using the personal pronouns in the Narrative text. The research subject is 37 students. They are from X-Science class of SMA Swasta Pencawan Medan in school years 2020/2021. There are 18 students who get very good score (score: 80-100). It can be stated into percentage form, there are 48.65 % of students who can get very good scores. Meanwhile there are 13 students who get good score (score: 70-79). It can be stated into percentage form that there are 35.14 % of students can achieve good score. 4 students get fair score (score: 60-69). It can be stated into percentage form, that there are 10.81 % of the students who can achieve fair scores. 2 students get low score (score: 50-59). It can be stated into percentage form that there are 5.41 % who get low scores. The total scores of the students are 2,870 and the mean scores is 77.57. It can be concluded that the students score generally is above KKM (Minimum Criteria of Mastery Learning). There are some factors that affect the abilty of the students in using the personal pronoun in the narrative text, they are: the students’ interested in learning narrative text, facilities in the school or used by the English teachers, students’ motivation, adequate time, and due to covid-19 pandemic, so the students’ have been joining virtual class (online class) until now. According to the students’ opinion, Virtual class is not very effective for students in learning English, especially when the students learn about the personal pronoun in narrative text. Key Words: An Analysis, Students’ Ability, Personal Pronoun, Narrative Text